2010
DOI: 10.1007/s11431-010-4069-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing aerodynamic performances of a high-turning compressor cascade via boundary layer suction

Abstract: Experimental investigation was carried out to study the effect of suction positions and suction flow rates on the aerodynamic performance of a compressor cascade with a large camber angle. The ink-trace flow visualization was conducted and the flow fields of the cascade were also measured. Three types of boundary layer suction configurations are compared, i.e. the suction surface suction, the endwall suction and the compound suction. Experimental results show that the large amount of suction flow rate gains mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…So EW1 is supposed to suck out more low-energy fluid and play a primary role in compound suction schemes. But the limited streamlines on the blades and EWs 18 illustrate that SS4 and EW1 & SS4 schemes are much more alike, especially when total suction flow rate is small, i.e., m suc = 0.5%. The suction flow distribution between EW1 & SS4 and corresponding aerodynamic parameters under different total suction flow rates in the EW1 and SS4 schemes are compared in Table 2 and Figure 10.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…So EW1 is supposed to suck out more low-energy fluid and play a primary role in compound suction schemes. But the limited streamlines on the blades and EWs 18 illustrate that SS4 and EW1 & SS4 schemes are much more alike, especially when total suction flow rate is small, i.e., m suc = 0.5%. The suction flow distribution between EW1 & SS4 and corresponding aerodynamic parameters under different total suction flow rates in the EW1 and SS4 schemes are compared in Table 2 and Figure 10.…”
Section: Resultsmentioning
confidence: 99%
“…It should be emphasized that upper and lower boundaries of the vacuum are separately defined as wall and outlet with certain amount of mass flow rate, which is in line with the real condition of the corresponding experiments. 18 This kind of suction manner is denoted by “one-side-suction” in the followed text. It is confirmed after this study that the passage flow still keeps symmetrical under one-side-suction manner under proper design.…”
Section: Numerical Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the reduced boundary layer will accelerate the migration of boundary layer, and the power generated by the suction plenum was reduced by the blade lean. Guo et al 20,21 investigated the different effects of compound and single scheme on the loss control in a subsonic stator. It suggested that both the boundary layer around the mid span and corner separation were removed by the suction slots.…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al [15][16][17] carried out experimental research both on the blade suction surface and on the endwall and found that the compound suction scheme works better with high suction flow rates compared with a single slot. A pitchwise endwall suction slot drilled at 13% chord upstream of the cascade was also investigated.…”
Section: Introductionmentioning
confidence: 99%